Análisis de la calidad de servicio en el establecimiento hotelero REEC mediante el modelo servqual. - Castro Castillo, Katherine Estefania (My University, 2021)
The hotel industry is one of the sectors that contributes most to the socio-economic development of the country. Working on the quality of service is essential, as its success is measured through the satisfaction obtained by the guest or client on fulfilling their expectations with regard to the service that has been provided. It is complex for a hotel to make the intangible tangible because it does not offer goods but services, however, there are strategies that allow measuring the quality of the services together with the participation of human talent and technology, having trained personnel and the necessary resources will project the company to the fulfilment of its objectives. For this reason, an in-depth analysis of bibliographical research has been carried out to identify the importance of quality in hotel services and the measurement of quality in the Hotel REEC in the city of Machala, through bibliographical research with a qualitative-quantitative approach, and the use of techniques such as data collection, surveys based on the SERVQUAL model and an observation sheet of the study area.
La industria hotelera es uno de los sectores que más aportan a la desarrollo socio económico del país, trabajar en la calidad del servicio es indispensable, pues su éxito se mide a través de la satisfacción que obtenga el huésped o cliente al cumplir sus expectativas frente al servicio que se ha brindado. Es complejo para un hotel volver tangible lo intangible porque no ofrece bienes sino servicios, no obstante, existen estrategias que permitan medir la calidad de los servicios conjuntamente con la participación del talento humano y la tecnología, contar con personal capacitado y con los recursos necesario proyectará a la empresa al cumplimiento de sus objetivos. Por tal razón se ha realizado un análisis profundo de investigación bibliográfica para analizar la importancia de la calidad en el los servicios hoteleros y la medición de la calidad en el Hotel REEC en la ciudad de Machala, A través de una investigación bibliográfica con enfoque cualitativo-cuantitativo, y el uso de técnicas como la recolección de datos, encuestas en base al modelo SERVQUAL y ficha de observación de la zona de estudio.
Keywords: SECTOR HOTELERO; SERVICIO; CALIDAD; TALENTO HUMANO